(untitled) (International Journal of Environmental Sciences, 2025)
Abstract Elevated blood sugar levels are the hallmark of type 2 diabetes mellirus (t2dm), a chronic metabolic illness that may have devastating consequences. Critical features of diabetes care include keeping blood glucose levels under control and lowering cardiovascular risk factors. Ascorbic acid is a well-known antioxidant and free radical scavenger that may be found in many plant foods. Protecting against oxidative stress, which is exacerbated in diabetics, is one of its most important functions. In recent years, interest in Vit. E’s antioxidant properties iainst oxidative damage to cell membranes and lipids has increased. Vit. E supplementation has been shown to improve insulin sensitivity and lipid profiles in persons witı’pe 2 diabetes, which may lower their risk of cardiovascular disease. Comparing the effects of ascorbic acid and Vit. e supplementation on glycemic control and cardiovascular risk in type 2 diabetes mellitus is the focus of this study.